Alforrias: mulheres libertas na Comarca de Santarém (1871–1888) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This paper deals with the manumissions granted to women in the district of Santarém between 1871 and 1888. This period is particularly significant due to the enactment of the Lei do Ventre Livre in 1871, which marked an important step in the transition towards the abolition of slavery in Brazil. The choice of the theme is justified by the need to understand how women's manumissions were granted, since far from being passive victims, enslaved women developed complex and even dangerous strategies to achieve their freedom. The main objective of this study is to analyze the dynamics and processes that led to the manumission of enslaved women in a given historical context in order to understand their strategies and motivations. It also seeks to understand the variations that influenced the granting of manumissions and the impact of these liberations on the lives of these women. The results reveal that, despite adversities, many freed women manage to establish solidarity networks and find means of subsistence. The analysis of the documents showed that factors such as age, specific skills and personal specifications influenced the granting of manumissions. The life stories of these women demonstrate incredible resilience and adaptability. The discussion of the results in light of the existing historiography allowed us to identify personalities and differences with other regions of Brazil. The condition of freed women in Santarém presents particularities that enrich the understanding of the dynamics of manumissions in the 19th century.
Keywords: Alforrias; Mulheres; Negras; Santarém; Século XIX; CNPQ::CIÊNCIAS HUMANAS